Colombia : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation discusses Colombia's economy that is improving drastically and is supported by very strong policy frameworks and well-executed policies. The recovery is gaining momentum and external imbalances have widened. Despite weaker-than-expected external demand, activity is expected to accelerate in 2019. Rebounding investment, continued policy support, and substantial migration from Venezuela are expected to lift growth to 3.6 percent while the current account deficit is expected to remain wide. The authorities expect the recovery to gather momentum in 2019 and inflation to remain close to target. Structural reforms are needed to boost inclusive growth and enhance external competitiveness. Addressing infrastructure gaps, strengthening governance and the rule of law, reducing informality, and enhancing customs and other trade practices are crucial. The draft National Development Plan rightly identifies key priorities and lays out a roadmap for reforms.